Faktor Pengaruh Reputasi dan Kualitas Layanan Terhadap Minat Beli Ulang Konsumen Pada Platform E-commerce Shopee - David Nurmanto; Heru Mulyanto; Tri Ngudi Wiyatno; Pupung Purnamasari; Hamzah Muhammad Mardi Putra (Jurnal Kajian Ilmiah, 2024)
The use of technology and the internet in the era of the industrial revolution 4.0 has the potential to improve product marketing strategies. E-commerce, as a product sales platform, is currently becoming popular and widely used. The number of e-commerce users continues to grow because of the ease of getting the desired product. Low interest in repurchasing needs to be considered in management's perspective to improve strategic planning and company services. The researchers point out that repurchase intentions are a much-studied topic in the current era of globalization. For this reason, this research will examine the influence of brand reputation and service quality on repurchase interest on the Shopee e-commerce platform. Data processing using SmartPLS software. The results of the validity and reliability tests for the indicators used showed validity and reliability and the results of the classical assumption test showed no multicollinearity in the variables. The results of the hypothesis test partially show that brand reputation does not have a significant influence on repurchase interest, while service quality has a significant influence on repurchase interest.